Render unto Rome : the secret life of money in the Catholic Church - Berry, Jason (New York : Crown Publishers, 2011)
Examines the way finances are managed in the Catholic Church, arguing that the organization is being damaged by secrecy and irresponsible decisions.
Includes bibliographical references and index.
Keywords: Catholic Church -- Finance; Catholic Church -- Corrupt practices